A Multi-Systems Approach to Human Movement after ACL Reconstruction: The Musculoskeletal System - Daniel Larson; Vien Vu; Brandon M Ness; Elizabeth Wellsandt; Scot Morrison (North American Sports Medicine Institute, 2021)
Several negative adaptations to the musculoskeletal system occur following anterior cruciate ligament (ACL) injury and ACL reconstruction (ACLR) such as arthrogenic muscle inhibition, decreased lower extremity muscle size, strength, power, as well as alterations to bone and cartilage. These changes have been associated with worse functional outcomes, altered biomechanics, and increased risk for re-injury and post-traumatic osteoarthritis. After ACL injury and subsequent ACLR, examination and evaluation of the musculoskeletal system is paramount to guiding clinical decision making during the rehabilitation and the return to sport process. The lack of access many clinicians have to devices necessary for gold standard assessment of muscle capacities and force profiles is often perceived as a significant barrier to best practices. Fortunately, testing for deficits can be accomplished with methods available to the clinician without access to costly equipment or time-intensive procedures. Interventions to address musculoskeletal system deficits can be implemented with a periodized program. This allows for restoration of physical capacities by adequately developing and emphasizing physical qualities beginning with mobility and movement, and progressing to work capacity and neuromuscular re-education, strength, explosive strength, and elastic or reactive strength. Additional considerations to aid in addressing strength deficits will be discussed such as neuromuscular electrical stimulation, volume and intensity, eccentric training, training to failure, cross-education, and biomechanical considerations. The American Physical Therapy Association adopted a new vision statement in 2013 which supported further development of the profession's identity by promoting the movement system, yet validation of the movement system has remained a challenge. Application of a multi-physiologic systems approach may offer a unique understanding of the musculoskeletal system and its integration with other body systems after ACLR. The purpose of this clinical commentary is to highlight important musculoskeletal system considerations within a multi-physiologic system approach to human movement following ACLR. # Level of Evidence 5